Optimizing Mechanical Properties and Environmental Benefits of CFBFA Composite Gravels Through Gypsum, Hydrated Lime Addition, and CO2 Carbonation Curing - Nuo Xu; Yuqing He; Rentuoya Sa; Nana Wang; Yuandong Yang; Suxia Ma (Solids)
This study explores the potential of utilizing circulating fluidized bed boiler fly ash (CFBFA) in the production of composite gravels, with the aim of achieving performance comparable to natural gravel while promoting sustainability. CFBFA, activated by hydrated lime and gypsum, was investigated for its pozzolanic reaction and carbonation curing under simulated coal-fired power plant flue gas conditions (80 °C, 0.4 MPa, 15% CO2, 85% N2). The study focused on optimizing the ratios of gypsum and hydrated lime in CFBFA-based cementitious materials, with the goal of enhancing their mechanical properties and understanding the underlying hydration and carbonation mechanisms. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to analyze the mineral composition and microstructure of the composite gravels. The results revealed that the optimal gypsum-to-hydrated lime ratio for CFBFA composite gravels is 2:1, achieving a compressive strength of 9.01 MPa after 28 days of carbonation curing. Carbonation curing accelerated hydration, improving the material’s strength, stability, and microstructure. Additionally, the production of CFBFA composite gravels demonstrated significant environmental benefits, reducing Cumulative Energy Demand (CED) by 86.52% and Global Warming Potential (GWP) by 87.81% compared to cement road base materials. This research underscores the potential of CFBFA as a sustainable construction material, with insights into improving its mechanical performance and expanding its large-scale use through carbonation curing with flue gas.